Majalah Tempo dan Manifestasi Fungsi Pers melalui Jurnalisme Pengawasan: Systematic Literature Review - Fadhil Muhammad (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2026)
Abstract Indonesia is a democratic nation, yet the implementation of press freedom has frequently been put to the test, ranging from media suppression during the New Order era to various challenges in the Reform era. Tempo Magazine, an independent media outlet, strives to realize press freedom as the Fourth Estate of Democracy through Watchdog Journalism. This study aims to analyze the consistency of Tempo Magazine in practicing Watchdog Journalism across different political eras. Using a systematic literature review, the findings indicate that Tempo’s consistency is particularly evident through its sharp criticism of the government, including its management and handling of the COVID-19 pandemic. Another aspect through which Tempo maintains the sharpness of its reporting is its editorial process and reporting mechanisms, which are always grounded in facts, data, and the accuracy of information in news production.  This demonstrates that media independence is crucial; the media has no responsibility to polish the government’s image, but rather to uphold press freedom, public trust, and realize democracy. The contribution of this research lies in strengthening the study of political communication and critical journalism in Indonesia, particularly regarding the practice of Watchdog Journalism within the context of democracy and press freedom.